(3QSGFd gfOSjIs - (3nhrjnLf Hf QSJe Gdochgj (B( (3Gdbhgj (B) (3, CHh Sgd,J (B390 (3g` s ((3OeTb s)
(3ChdgG (B:s
(3HYO GdHSedI hGdOjHGLI deG cGf GdYde HeSGMI GdGLSGe hGdCTcGd GdebGOjQ JfSH HYVgG Gdj HYV bHd GdYde HeQGcR GKbGdgG s
(3BNQgG (B:s
(3aEfg SjfJgj Gdj ebOGQ CUZQ ef GdebOGQ GdCUZQ MJj jchf GdHQgGf YGekG s
(3Vef eLehY , JQJjHgG (B: 8s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdNGeSs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B8 - (3U (B127 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B13 - (3U (B175s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdQjGVjGJs